Big Five Personality Characteristics and Its Effect on Task Conflict: A Case Study of Telecom Companies - NAILA SAYYED; SAQIB SHAHZAD; IHTESHAM KHAN; DR. JEHANGIR (Journal of Business & Tourism, 2021)
The study was an attempt to find out the effect of Myers Briggs Big Five personality characteristics on task conflict. The employees working in the telecommunication sector were considered as the population of the study. The employees were selected randomly. 180 questionnaires were distributed among employees. 127 properly filled questionnaires were received back from the respondents. The response rate was 70.56 percent. Simple Random sampling technique was used for the study. Analysis was used to testify the hypotheses of the study. As per the results of regression analysis big five personality characteristics were found to have significant effect on task conflict.